Transforming Waste into Solutions: Raw and Modified Bioadsorbents for Emerging Contaminant Removal - Villamar-Ayala, C (Elsevier Ltd, 2025)
The presence of emerging contaminants (ECs) in water bodies has raised growing concerns due to their persistence, bioaccumulative potential, and adverse ecological and human health effects. Conventional treatment technologies often fail to efficiently remove these contaminants, necessitating the exploration of alternative approaches. In this context, bioadsorption has emerged as a cost-effective and sustainable method for EC removal. This review comprehensively examines the application of raw and modified agro-industrial and industrial residues as bioadsorbents for the adsorption of pharmaceuticals, personal care products, pesticides, and steroid hormones. The reviewed articles explore various methods for processing and modification methods for adsorbent materials, complemented by investigations into adsorption conditions, equilibrium behavior, and key adsorption mechanisms - such as hydrogen bonding, pore filling, electrostatic interactions, hydrophobic attraction, and π-πinteractions. Special attention is given to the influence of material properties, including surface area, porosity, and the presence and enhancement of functional groups through various modification strategies. Additionally, the economic feasibility and environmental implications of bioadsorbent utilization are discussed, highlighting challenges in large-scale implementation. This study provides a holistic perspective on bioadsorption as a promising strategy for wastewater treatment, offering insights into optimizing bioadsorbent performance while promoting circular economy principles in environmental remediation. © 2025 The Authors.